2009
DOI: 10.1111/j.1439-0523.2009.01716.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci and epistatic interactions in barley conferring resistance to net type net blotch (Pyrenophora teres f. teres) isolates

Abstract: Net type net blotch (NTNB) is an important barley disease in Australia and elsewhere, with significant yield reduction. This trait is important in selection along with other traits of quality and agronomic value. Two-hundred doubled-haploid lines were generated through anther culture from a cross between ÔPompadourÕ and ÔStirlingÕ. Quantitative trait loci (QTL) were identified against five isolates of Pyrenophora teres f. teres, which represent virulences across Australia. QTL were mapped on chromosomes 3H and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Our earlier work on mapping resistance genes from ‘Pompadour’ and ‘Stirling’ (Gupta et al. 2010) detected contributions of 6H and 3H loci for NTNB resistance.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our earlier work on mapping resistance genes from ‘Pompadour’ and ‘Stirling’ (Gupta et al. 2010) detected contributions of 6H and 3H loci for NTNB resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have identified NTNB resistance genes on all seven barley chromosomes using different molecular techniques (Graner et al 1996, Steffenson et al 1996, Richter et al 1998, Spaner et al 1998, Manninen et al 2000, Ma et al 2004, Friesen et al 2006, Grewal et al 2008, St Pierre et al 2010). Similarly, NTNB resistance genes on 2H, 3H, 4H and 6H were also identified in Australian cultivars at seedling and adult stages (Cakir et al 2003a, Raman et al 2003, Emebiri et al 2005, Lehmensiek et al 2007, Gupta et al 2010.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The 6H QTL region has been reported in several previous studies using a variety of host populations and pathogen isolates (see review by Liu et al ., ). It is likely that multiple resistance/susceptibility genes are present at the 6H locus, not only because of the number of reports of the 6H region, but also because of the report of this region harbouring both dominant and recessive forms of resistance (Abu Qamar et al ., ; Friesen et al ., ; Gupta et al ., ; St. Pierre et al ., ). In the current study, we found that the 6H association with susceptibility was identified for six of the 10 isolates tested, with these six being geographically diverse.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies using various RIL and doubled haploid (DH) mapping populations have identified a region on chromosome 3H which, on the basis of common markers, appears to be in the same region as the major 3H QTLs reported here (Graner et al ., ; Gupta et al ., , ; Raman et al ., ; Yun et al ., ). At least three of these studies also used the Australian isolate NB50 (Gupta et al ., , ; Raman et al ., ). Using this same NB50 isolate on the HN population, we also detected a major QTL on 3H ( R 2 = 0.66) in addition to two minor effect QTLs on 3HL and 5HS.…”
Section: Discussionmentioning
confidence: 99%